Effect of vitamin D on cognitive function and white matter hyperintensity in patients with mild Alzheimer's disease. Issue 1 (26th November 2019) - Shih, En‐Jie; Lee, Wei‐Ju; Hsu, Jung‐Lung; Wang, Shuu‐Jiun; Fuh, Jong‐Ling
Abstract : Aim: To examine the effect of vitamin D level on cognitive function and white matter hyperintensity (WMH) in patients with mild Alzheimer's disease (AD). Methods: We recruited patients with mild AD, and carried out clinical interviews, neuropsychological assessments, laboratory tests and brain magnetic resonance imaging. Results: In total, 146 patients with mild AD (68 men, 78 women; mean age 79.1 ± 7.0 years; mean education 10.2 ± 4.3 years) were enlisted. The mean Mini‐Mental State Examination (MMSE) score was 21.0 ± 3.8. The 25‐hydroxy vitamin D (25[OH]D) level was correlated negatively with the WMH volume (β = −0.219, P = 0.004) after adjusting for age, sex, years of education, apolipoprotein ε4 allele status, seasons of blood sampling, hypertension, diabetes mellitus, hyperlipidemia, coronary heart disease and total brain volume. The 25(OH)D level was correlated positively with the MMSE score (β = 0.309, P < 0.001) after adjusting for the same covariates. Multivariate regression analysis with the MMSE score serving as the dependent variable and adjustment for covariates showed that the 25(OH)D level was an independent predictor of the MMSE score (β = 0.322, P < 0.001), but the WMH volume was not (β = 0.056, P = 0.587). These findings suggest that WMH has no mediation effect between the 25(OH)D level and the MMSE score. Conclusions: Reduced plasma 25(OH)D levels were associated with low MMSE scores in patients with mild AD, but the underlying mechanism is not attributable to WMH. Thus, it suggested that the presence of another pathomechanism exists. Geriatr Gerontol Int 2020; 20: 52–58 .